PWE-102 Elucidating The Role of Non JEJUNI/Coli-Campylobacter in The Development of Colorectal Cancer Utilising Comparative Genomics to Study Their Pathogenic Potential. (17th August 2016) - Mukhopadhya, I; Hsu, T; Nielsen, H; Nielsen, H; Berry, S; Huttenhower, C; Hold, GL
Abstract : Introduction: Emerging evidence links the gut microbiota to colonic inflammation and colorectal cancer (CRC). Studies have shown over-representation of oral bacterial species including Campylobacter spp. in CRC tissue and also njc- Campylobacter are over-represented in IBD wherein normal homeostasis has been lost. Understanding the role of njc -Campylobacter as an aetiological agent in CRC and elucidating their pathogenicity characteristics is of immense clinical importance. Aim: To perform whole genome sequencing (WGS) of clinically derived njc- Campylobacter to compare/identify virulence traits potentially linked to disease presentation. Methods: WGS of 21 unique clinically derived Campylobacter isolates was performed (7 Campylobacter showae, 3 Campylobacter ureolyticus and 11 Campylobacter concisus ) from biopsy/faecal samples of subjects with malignancy, acute enteritis and IBD. DNA was extracted using the QIAamp DNA Mini Kit. Libraries were prepared using Illumina Nextera XT DNA Library Prep Kit and Nextera XT Index Kit v2, multiplexed, and paired-end sequenced on the Illumina MiSeq. De novo read assembly used the A5-miseq pipeline with QUAST. Genome annotation was performed using the rapid prokaryotic genome annotation tool Prokka. Results: Genome assembly of C. showae strains resulted in 8 to 59 contigs per strain (mean number = 21; average genome size 2, 199, 446 nucleotides); C. concisus isolates had an average contig number of 72 and average genome size of 1, 982, 586 nucleotides. C. ureolyticus strains average contig number was 134 and average genome size of 1, 608, 008 nucleotides. Through Prokka annotation, the average number of coding sequences was 2215 for C. showae isolates (range 2050–2368) with function predicted for 71.3%. For C. concisus the average number of coding sequences was 1985 (range 1833–2087) with function predicted for 71.9%. C. ureolyticus had a lower number of coding sequences (average 1613) with function predicted for 72.6%. We focused on the VirB4/D10 operon homologs, which are components of the Type IV secretion system. Contrary to previously published sequence data from oral strains, the majority of colonic C. showae isolated and 2 C . concisus strains possessed almost complete T4SS systems and additional virulence traits, including the exotoxin 9 gene. Conclusion: The findings clearly demonstrate genetic differences among colonic Campylobacter isolates as compared to oral strains and sheds light on the pathogenic potential of these emerging colonic pathogens. The findings also further highlight the need for further sequencing studies to be undertaken. Disclosure of Interest: None Declared